Breastfeeding Duration and Its Effective Factors in Kerman Province, Iran. (November 2022) - Mirafzali, Sedigheh; Akbari Sari, Ali; Iranpour, Abedin; Alizadeh, Somayeh
Introduction: Complete cessation of breastfeeding (CCB) at the right time is as important as starting breastfeeding, as well as identifying the factors that affect the duration of breastfeeding, so that breastfeeding promotion programs focus on these causes, to increase mothers' ability and desire to breastfeed. This study aimed to determine the time of CCB and its related factors. Methods: This analytical cross-sectional study was conducted in 2020. This study was performed at all health centers and health homes affiliated to Kerman University of Medical Sciences, in Kerman province, Iran. A total of 802 urban and rural mothers with children aged from 30 to 36 months completed the questionnaire. The validity and reliability of the questionnaire were confirmed by Cronbach's alpha of 85%. Data were analyzed using SPSS software version 16. Results: The mean time of breastfeeding was 19.23 ± 7.09 months and the median was 22-month-year. About 41% of children were breastfed until 24-month. There was a significant relationship between the time of CCB with contraception, number of households, place of residence, and weight at 6-month at the level of 0.05. Conclusion: Duration of breastfeeding is influenced by some demographic and cultural factors. The timing of the CCB is near to the suggestions of the World Health Organization (WHO) and religious teachings.